Managing transitions : the Chinese Communist Party, united front work, corporatism, and hegemony - Groot, Gerry, 1960- (East Asia (New York, N.Y.), 2004)
Examines the history and roles of China's minor parties and groups in the Chinese Communist Party's united front between the 1930 and 1990 using Antonio Gramsci's principles for the winning and maintaining of hegemony.